Global‐scale convective aggregation: Implications for the Madden‐Julian Oscillation. (12th October 2015) - Arnold, Nathan P.; Randall, David A.
Abstract: Previous work has shown that convection will self‐organize in cloud‐system‐resolving model simulations of radiative‐convective equilibrium, and it has been suggested that the convective envelope of the Madden‐Julian oscillation (MJO) may be organized by similar processes on a much larger scale. Here we present support for that hypothesis based on simulations with SP‐CAM with globally uniform SST. Without rotation, convection self‐organizes into large (∼4000 km) clusters surrounded by dry regions, while with Earth‐like rotation the model produces a robust MJO. The nonrotating aggregation and MJO are found to have similar budgets of moist static energy, both being supported by diabatic feedbacks, particularly cloud‐longwave interaction. Mechanism denial experiments show that longwave heating anomalies associated with high clouds are essential to the nonrotating aggregation, and amplify the MJO. Simulations using the conventional CAM show a weaker MJO and a much weaker tendency for nonrotating aggregation, and both MJO activity and aggregation intensity are found to increase with the entrainment rate in the deep convection parameterization. Key Points: Nonrotating convective aggregation occurs on scales of ∼4000 km Aggregation is supported by a cloud‐longwave feedback and a shallow circulation. The MJO and aggregation both depend on the convective entrainment rate